Solution of prey–predator problem by numeric–analytic technique - Chowdhury, Md. Sazzad Hossien; Hashim, Ishak; Mawa, S. (Elsevier, 2009)
In this paper, an analytical expression for the solution of the prey–predator problem by an adaptation of the classical Adomian decomposition method (ADM). The ADM is treated as an algorithm for approximating the solution of the problem in a sequence of time intervals, i.e. the classical ADM is converted into a hybrid numeric–analytic method called the multistage ADM (MADM). Numerical comparisons with the classical ADM, and the classical fourth-order Rungge– Kutta (RK4) methods are presented.